Differential Strategies to Tolerate Flooding in Polygonum hydropiper Plants Originating From Low- and High-Elevation Habitats - Chen, Xin-Sheng; Li, Ya-Fang; Cai, Yun-He; Xie, Yong-Hong; Deng, Zheng-Miao; Li, Feng; Hou, Zhi-Yong (Frontiers in Plant Science, 2019)
In species that occur over a wide range of flooding conditions, plant populations may have evolved divergent strategies as a consequence of long-term adaptation to local flooding conditions. In the present study, we investigated the effects of a flooding gradient on the growth and carbohydrate reserves of Polygonum hydropiper plants originating from low- and high-elevation habitats in the Dongting Lake wetlands. The results indicated that shoot length did not differ, whereas the total biomass and carbohydrate reserves were reduced under flooded compared to well-drained conditions for plants originating from both habitat types. However, shoot length, shoot mass, rhizome mass, and total biomass were lower in plants from low-elevation habitats than in those from high-elevation habitats in the flooded condition. Soluble sugar and starch contents in belowground biomass were higher in plants from low-elevation habitats than in those from high-elevation habitats independently of the water level. Therefore, P. hydropiper plants from low-elevation habitats exhibit a lower growth rate and more conservative energy strategy to cope with flooding in comparison with plants from high-elevation habitats. Differential strategies to cope with flooding among P. hydropiper populations are most likely a response to the flooding pressures of the habitat of origin and may potentially drive ecotype differentiation within species along flooding gradients.